Extracellular proteoglycan decorin maintains human hair follicle stem cells. Issue 12 (15th October 2018) - Miyachi, Katsuma; Yamada, Takaaki; Kawagishi‐Hotta, Mika; Hasebe, Yuichi; Date, Yasushi; Hasegawa, Seiji; Arima, Masaru; Iwata, Yohei; Kobayashi, Tsukane; Numata, Shigeki; Yamamoto, Naoki; Nakata, Satoru; et al.
Abstract: Hair follicle stem cells (HFSC) are localized in the bulge region of the hair follicle and play a role in producing hair. Recently, it has been shown that the number of HFSC decreases with age, which is thought to be a cause of senile alopecia. Therefore, maintaining HFSC may be key for the prevention of age‐related hair loss, but the regulatory mechanisms of HFSC and the effects of aging on them are largely unknown. In general, stem cells are known to require regulatory factors in the pericellular microenvironment, termed the stem cell niche, to maintain their cell function. In this study, we focused on the extracellular matrix proteoglycan decorin (DCN) as a candidate factor for maintaining the human HFSC niche. Gene expression analysis showed that DCN was highly expressed in the bulge region. We observed decreases in DCN expression as well as the number of KRT15‐positive HFSC with age. In vitro experiments with human plucked hair‐derived HFSC revealed that HFSC lost their undifferentiated state with increasing passages, and prior to this change a decrease in DCN expression was observed. Furthermore, knockdown of DCN promoted HFSC differentiation. In contrast, when HFSC were cultured on DCN‐coated plates, they showed an even more undifferentiated state. From these results, as a novel mechanism for maintaining HFSC, it was suggested that DCN functions as a stem cell niche component, and that the deficit of HFSC maintenance caused by a reduction in DCN expression could be a cause of age‐related hair loss.